Peran Orang Tua Kristen Dalam Pendidikan Agama: Perspektif Dari Pemimpin Gereja Dan Pendidik - Juwita Kadang; Wati Wati; Risda Risda; Astriani Tando; Yegi Pabua; Milka Para'da (Jurnal Pendidikan Agama dan Teologi, 2023)
Parents must play an important role in Christian Religion education, the first and foremost educational environment for a child, namely in the family. The method used in this study is the Systemic Literature Review Method, namely by finding facts with fixed interpretations. The results of the study show that the Role of Christian Parents in Religious Education: The Perspective of Church Leaders and Educators is as follows. The Perspective of Church Leaders: Church leaders believe that parents have a central role in teaching religion to their children. For example Models of Faith, Prayer and Family Service, Bible Education, Participation in the Church while from the perspective of educators it consists of Learning Support, Open Communication, Religious Experience